Chapter Attraverso la porta di Lisbona: i generi coloniali volano del commercio luso-genovese tra XVII e XVIII secolo - CALCAGNO, Paolo (Atti delle «Settimane di Studi» e altri Convegni, 2019)
Approaching the subject from a diachronic perspective, the essay sets out to outline a chronology of the Mediterranean prominence in the sugar trade considering port activity and commercial elites. Studies carried out so far, backed by important findings sourced from custom records and private correspondence, attest Genoa's undisputed leadership during the central decades of the eighteenth century, when Brazilian sugar production grew at exponential rates turning this trade into one of the greatest "businesses" of the time.